A case of high-pressure intracerebral pouch. Issue 10 (October 1981) - Al-Din, A N; Williams, B
Abstract : A case is presented of a 13-year-old boy with a long-standing high-pressure pouch in the right parietal lobe containing cerebrospinal fluid. The clinical presentation was of epilepsy. Isotopic studies suggested that the pouch was filling along the subarachnoid space at the back of the corpus callosum in the posterior part of the interhemispheric fissure. There was a dilated sulcus at this point, which filled freely on air encephalography. Pressure studies suggested the likelihood of a venous pulsation filling mechanism with a valvular action. Electrocorticography, excision of an epileptic focus in the wall of the cavity and opening of the ventricular wall into the pouch have produced a good clinical result. Computerized tomography after operation has confirmed correction of the high-pressure state.